2002
DOI: 10.1093/gerona/57.2.m138
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Use of Digoxin in Older Hospitalized Heart Failure Patients

Abstract: Background. Older adults are more likely to suffer from the adverse effects of digoxin. Studies have described the inappropriate use of digoxin in various populations. The objective of this study was to determine the correlates of inappropriate digoxin use in older heart failure patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…A systematic review of 35 educational intervention studies for patients with HF demonstrated that education improved knowledge, self-monitoring, medication adherence, time to hospitalization, and days in the hospital. 363 Patients who receive in-hospital education have higher knowledge scores at discharge and 1 year later when compared with those who did not receive in-hospital education. 364 Data have called into question the survival benefit of discharge education.…”
Section: Management Strategies For Stage Bmentioning
confidence: 92%
See 1 more Smart Citation
“…A systematic review of 35 educational intervention studies for patients with HF demonstrated that education improved knowledge, self-monitoring, medication adherence, time to hospitalization, and days in the hospital. 363 Patients who receive in-hospital education have higher knowledge scores at discharge and 1 year later when compared with those who did not receive in-hospital education. 364 Data have called into question the survival benefit of discharge education.…”
Section: Management Strategies For Stage Bmentioning
confidence: 92%
“…363 Patients need to understand how to monitor their symptoms and weight fluctuations, restrict their sodium intake, take their medications as prescribed, and stay physically active. Education regarding these recommendations is necessary, albeit not always sufficient, to significantly improve outcomes.…”
Section: Management Strategies For Stage Bmentioning
confidence: 99%
“…8 Of 376 hospitalized patients with heart failure receiving digoxin, 223 (37%) had no appropriate indication for its use. 9 Therapeutic concentrations of digoxin do not decrease the frequency of episodes of paroxysmal AF or the duration of episodes of paroxysmal AF diagnosed by 24-h ambulatory electrocardiograms. 4,5 Digoxin has been shown to increase the duration of episodes of paroxysmal AF, a result consistent with its action in reducing the atrial refractory period.…”
Section: Discussionmentioning
confidence: 95%
“…This is in line with the current still large use of this drug, despite the alert of a narrower therapeutic window in old patients. 17 The higher prevalence of atrial fibrillation in the older group probably does not account for this tendency and this is underlined in both groups by the reduction of digoxin therapy at discharge of the patients who were on digoxin treatment at admission.…”
Section: Discussionmentioning
confidence: 98%